An analysis of the challenges faced by banks in managing credit in Zimbabwe - Mavhiki, Severino; Mapetere, Denver; Mhonde, Christopher (IISTE, 2021)
The purpose of the study is to analyse the challenges facing banks in managing credit in Zimbabwe in the wake of the multicurrency regime that was introduced in the year 2009. The study is relevant considering that banks have an important role of financing the undercapitalised productive sectors .The chi-square is used to establish the relationship between the banks' lending decisions and the level of exposure. The results of the study suggest that increasing lending by banks exposes them to high risk of failure. The findings of this study have important implications for policy makers and banks in Zimbabwe.